2017
DOI: 10.1002/jcad.12127
|View full text |Cite
|
Sign up to set email alerts
|

Latina/o College Students' Perceptions of Career Barriers: Influence of Ethnic Identity, Acculturation, and Self‐Efficacy

Abstract: Path analysis was used to explore the tenets of social cognitive career theory with a sample of 357 Latina/o college students. A modified path model revealed that career decision self-efficacy (CDSE) mediated the influence of ethnic identity and acculturation level on the perception of career barriers. The findings point to the role of ethnic identity in augmenting Latina/o college students' CDSE and increasing awareness about career barriers. Implications for theory, research, and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Previous research has also identified the need to bolster student preparation and connectedness, decrease financial barriers, and improve the presence and efforts of program-level interventions targeting student retention as a means of ameliorating possible barriers to success (Burns, 2010). Career service providers (e.g., counselors, college counselors, career advisors, and counseling psychologists) may help by intervening at the individual and system levels, such as through advocacy efforts (e.g., advocating for increased funding, mentorship and internship opportunities, and institutional supports and affirming policies) and bolstering students’ self-efficacy and coping skills surrounding coping with these barriers (Mejia-Smith & Gushue, 2017). To this latter point, given the heightened perception of barriers in community college students, particularly those of color, relative to their four-year university counterparts, community college students would benefit from having a safe space to discuss and explore the extent to which barriers affect them and methods for dealing with the accompanying external and internal demands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also identified the need to bolster student preparation and connectedness, decrease financial barriers, and improve the presence and efforts of program-level interventions targeting student retention as a means of ameliorating possible barriers to success (Burns, 2010). Career service providers (e.g., counselors, college counselors, career advisors, and counseling psychologists) may help by intervening at the individual and system levels, such as through advocacy efforts (e.g., advocating for increased funding, mentorship and internship opportunities, and institutional supports and affirming policies) and bolstering students’ self-efficacy and coping skills surrounding coping with these barriers (Mejia-Smith & Gushue, 2017). To this latter point, given the heightened perception of barriers in community college students, particularly those of color, relative to their four-year university counterparts, community college students would benefit from having a safe space to discuss and explore the extent to which barriers affect them and methods for dealing with the accompanying external and internal demands.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents indicated the extent to which they agree with items on a Likert-type 5-point scale ranging from 1 (strongly disagree) to 5 (strongly agree) with higher scores indicating perceptions of more barriers. Mejia-Smith and Gushue (2017) found that self-efficacy was negatively related to perceptions of barriers among a sample of primarily young adult Latinas. Luzzo and McWhirter (2001) have reported an internal consistency measured by Cronbach's alpha as .90 for the entire scale, and .86 for the career-related barriers subscale in a college sample of ethnic minority and European American students.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have examined various antecedents of career decidedness among emerging adults, including vocational identity (Vondracek et al, 1995), leisure and work engagement (Konstam & Lehmann, 2011), career selfefficacy (Luzzo, 1996;Xu & Tracey, 2015), and career adaptability and future orientation (Ginevera et al, 2016). Although there is much evidence for the linkage between career-related barriers and career decision selfefficacy (e.g., Gnilka & Novakovic, 2017;Mejia-Smith & Gushue, 2017;Wright et al, 2014), only a few studies have examined the effect of college students' perceptions of career-related barriers on their decision-making in future occupations (Creed et al, 2004;Holland et al, 1980). These studies suggest that career-related barriers have negative effects on FGC students' career decision-making.…”
Section: Purpose Of the Studymentioning
confidence: 99%